Magnitude of extreme heat waves in present climate and their projection in a warming world. Issue 22 (20th November 2014) - Russo, Simone; Dosio, Alessandro; Graversen, Rune G.; Sillmann, Jana; Carrao, Hugo; Dunbar, Martha B.; Singleton, Andrew; Montagna, Paolo; Barbola, Paulo; Vogt, Jürgen V.
Abstract: An extreme heat wave occurred in Russia in the summer of 2010. It had serious impacts on humans and natural ecosystems, it was the strongest recorded globally in recent decades and exceeded in amplitude and spatial extent the previous hottest European summer in 2003. Earlier studies have not succeeded in comparing the magnitude of heat waves across continents and in time. This study introduces a new Heat Wave Magnitude Index that can be compared over space and time. The index is based on the analysis of daily maximum temperature in order to classify the strongest heat waves that occurred worldwide during the three study periods 1980–1990, 1991–2001, and 2002–2012. In addition, multimodel ensemble outputs from the Coupled Model Intercomparison Project Phase 5 are used to project future occurrence and severity of heat waves, under different Representative Concentration Pathways, adopted by the Intergovernmental Panel on Climate Change for its Fifth Assessment Report (AR5). Results show that the percentage of global area affected by heat waves has increased in recent decades. Moreover, model predictions reveal an increase in the probability of occurrence of extreme and very extreme heat waves in the coming years, in particular, by the end of this century, under the most severe IPCC AR5 scenario, events of the same severity as that in Russia in the summer of 2010 will become the norm and are projected to occur as often as every 2 years for regions such as southern Europe, North America, South America, Africa, and Indonesia. Key Points: Definition of a new Heat Wave Magnitude Index Classification of the magnitude of the heat waves occurred in the present Prediction of heat wave magnitude under climate scenarios